Environmental Regulation and International Trade - Abay Mulatu; Raymond J.G.M. Florax; Cees A. Withagen (Tinbergen Institute, 2004)
We empirically investigate the responsiveness of international trade to the stringency of environmental regulation. Stringent environmental regulation may impair the export competitiveness of `dirty' domestic industries, and as a result, `pollution havens' emerge in countries where environmental regulation is `over-lax.' We examine the impact of pollution abatement and control costs on net exports in order to grasp this phenomenon. Theoretically, our analysis is related to a general equilibrium model of trade and pollution nesting the pollution haven motive for trade with the factor endowment motive. We analyze data on two-digit ISIC manufacturing industries during the period 1977–1992 in Germany, the Netherlands and the US, and show that trade patterns in `dirty' commodities are jointly determined by relative factor endowments and environmental stringency differentials.
Keywords: F14; L50; Q28; 330; Trade; competitiveness; environmental policy; pollution abatement; pollution haven; Internationale Wirtschaft; Export; Umweltschutz; Umweltpolitik; Wirkungsanalyse; USA; Deutschland; Niederlande